2022
DOI: 10.3390/microorganisms11010067
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of BPA Degradation and Toxicity Resistance in Rhodococcus equi

Abstract: Bisphenol A (BPA) pollution poses an increasingly serious problem. BPA has been detected in a variety of environmental media and human tissues. Microbial degradation is an effective method of environmental BPA remediation. However, BPA is also biotoxic to microorganisms. In this study, Rhodococcus equi DSSKP-R-001 (R-001) was used to degrade BPA, and the effects of BPA on the growth metabolism, gene expression patterns, and toxicity-resistance mechanisms of Rhodococcus equi were analyzed. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The soil system can self-restore and effectively manage external adverse changes, potentially surpassing the efficacy of the bioaugmentation method in the long term. Similarly, genes involved in aspects of the bisphenol A (another well-known endocrine disrupting compound often detected with NP/NPEOs)-resistance response, such as base excision repair, osmoprotectant transport, iron-complex transport, and some energy metabolisms, were upregulated to mitigate the loss of energy associated with the exposure ( Tian et al, 2023 ). More importantly, major shifts in bacterial function were caused by the NP concentration and, to a lesser extent, by the microbial agent NP-M2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The soil system can self-restore and effectively manage external adverse changes, potentially surpassing the efficacy of the bioaugmentation method in the long term. Similarly, genes involved in aspects of the bisphenol A (another well-known endocrine disrupting compound often detected with NP/NPEOs)-resistance response, such as base excision repair, osmoprotectant transport, iron-complex transport, and some energy metabolisms, were upregulated to mitigate the loss of energy associated with the exposure ( Tian et al, 2023 ). More importantly, major shifts in bacterial function were caused by the NP concentration and, to a lesser extent, by the microbial agent NP-M2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The interactions between BPA and microorganisms throughout the biodegradation process are indeed intricate; Microorganisms exhibited a range of metabolic control mechanisms aimed to countering and neutralizing BPA-induced stress; these mechanisms were orchestrated by the microbial community to adapted to and efficiently degraded BPA, thereby mitigating its adverse effects on the environment totally [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to B. subtilis , the growth of Lactococcus lactis , L. plantarum , Enterococcus faecalis , and Saccharomyces cerevisiae was also inhibited by increasing the BPA concentrations. It has been reported that BPA is toxic to microorganisms and inhibits their growth, metabolism, and gene expression [ 35 ]. BPA also appears to be a similar case to most toxic compounds that exhibit concentration-dependent inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymes involved in the microbial degradation of BPA vary depending on the genus or species, though three enzymes have mainly been reported to play an key role: (i) monooxygenases (e.g., cytochrome P450 and ammonia monooxygenase), (ii) oxidases (e.g., laccase and manganese oxidase), and (iii) peroxidases (e.g., lignin and manganese peroxidases) [ 33 , 35 , 42 , 43 ]. In the future, it is necessary to further study the enzymes and genes that are involved in the excellent BPA degradation performance of B. subtilis P74 through whole genome sequencing.…”
Section: Discussionmentioning
confidence: 99%